Bagaimana Kualitas Website Terhadap Kepercayaan Toko Online ? - Razi Fargly; R.A Marlien (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to examine the influence of company reputation, service quality, electronic word of mouth and web quality on study customer trust in Shopee customers in Semarang City. The population in this research is Shopee customers in the Semarang area with a total of 150 respondents. Primary data was obtained from a questionnaire distributed via Google Form using the Likert scale method from one to five. The research results show that company reputation, service quality, electronic word of mouth and web quality influence Shopee customer trust in Semarang City. Keywords: company reputation, service quality, electronic word of mouth and web quality, customer trust